[tex]a) \frac{x-2}{5} = 2 |*5\\x-2 =10 |+2\\x=12\\b)\frac{4t}{8}=1 |*8\\4t=8 | :4\\t=2\\c)\frac{4b-3}{3}=3 |*3\\4b-3=9 |+3\\4b=12|:4\\b=3\\d) 24+c:2=30 |-24\\c:2=6|*2c=12\\e)\frac{15}{d}=5 |*d\\15=5d|:5\\d=3\\f)\frac{6x+3}{6} =\frac{1}{3} |*6\\6x+3=2 |-3\\6x=-1|:6\\x=-\frac{1}{6} \\g)\frac{2m-4}{3} =\frac{m-2}{4} |*12\\4(2m-4)=3(m-2)\\8m-16=3m-6|-3m\\5m-16=-6|+16\\5m=10|:5\\m=2\\h)\frac{15x-10}{5} =10|*5\\15x-10=50|=10\\15x=60|:15\\x=4\\[/tex]
[tex]i) 27z:9-7=20 |+7\\27z:9=27|*9\\27z=243|:27\\z=9\\j)\frac{9x^{2} -3}{3}=74|*3\\ 9x^{2} -3=222|+3\\9x^{2} =225|:9\\x^{2} =25 |\sqrt{} \\x=5[/tex]